Pengaruh Penambahan Limbah Ampas Kopi Terhadap Koefisien Permeabilitas Tanah dan Piping - Yulis Hendrita Triana; Irwan Lie Keng Wong; Benyamin Tanan (Paulus Civil Engineering Journal, 2022)
Clay soil is soil that has certain mineral particles in which there are particles of silt and sand and there may also be a mixture of organic matter. This type of soil has a poor soil carrying capacity where the condition of the soil does not allow for a highway construction to be built on it. Efforts need to be made to improve the condition of the soil and one of the most commonly used ways is to stabilize the soil and the soil is taken in Lambanan Village, Mamasa District, Mamasa Regency, West Sulawesi then soil samples are mixed with coffee grounds with variations of 0%, 5%, 10%, 15%. The tests carried out are soil moisture content, soil specific gravity, atterberg boundaries, permeability and piping tests. In permeability testing, there is a decrease in the percentage value of permeability and in piping testing there is an increase in the percentage value of piping. In this study, it was seen that the addition of waste pulp.